Spectral Methods for the Estimation of the Effective Elastic Thickness of the Lithosphere - Kirby, Jonathan (Cham : Springer International Publishing : Imprint: Springer, 2022)
Although several excellent works exist that describe the effective elastic thickness (Te) of the lithosphere-its theory, significance and relevance to Earth sciences in general-none cover the details of the methods for its estimation. This book brings together the disparate knowledge required to estimate Te in one handy volume: signal processing, harmonic analysis, civil engineering, and foundational mathematics and physics, in addition to the relevant geophysics and, to a lesser extent, geology. Its two principal focus areas are spectral estimation, covering various approaches to estimating the admittance and coherence between gravity and topography using Slepian multitapers and fan wavelets; and algebraic and finite difference solutions of the plate bending partial differential equation in a variety of geological settings. This book would be suitable for postgraduate students beginning their research, up to faculty professors interested in diversifying their skills.
Isostasy, Flexure and Strength -- The Fourier Transform -- Multitaper Spectral Estimation -- The Continuous Wavelet Transform -- Admittance, Coherency and Coherence -- Map Projections -- Loading and Flexure of an Elastic Plate -- Gravity and Admittance of a Flexed Plate -- The Load Deconvolution Method -- Synthetic Testing -- Practical Te Estimation.
Keywords: Geology; Geotechnical engineering; Geology; Geotechnical Engineering and Applied Earth Sciences